"He Gently Leads those with Young": Life-Giving Principles from the Rule of Saint Benedict for Early Parenthood. Issue 1 (May 2016) - Brown, Jessica
After voicing a need for soul care that meets the rigors of early parenthood, this article looks to The Rule of Saint Benedict for three life-giving principles: togetherness, ordinariness, and prayer. Togetherness means not only the meta-vision of "doing" family in a larger community; it means transparency and willingness to ask for help. We learn ordinariness from Benedict through the vow of stability, which demands that our inner lives open and connect to the present moment, and also through the way Benedict honors menial tasks and vessels. The Opus Dei that the Rule weaves through all work can, for a parent, take the form of an organic Opus Dei, woven around the routines of childcare, as well as the great small-prayer practices of the church, like aspirations, Celtic prayers, the florilegia, and hesychastic prayer. These principles help early parenthood become an integral phase in our own formation and ability to care for another.